Faktor-faktor risiko penyakit trofoblas - Soeharyono, Soeharyono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
A case control study was carried out in Sardjito General Hospital Yogyakarta to evaluate the risk factors for gestational trophoblastic disease. One hundred and seven cases of trophoblastic diseases fulfilling the inclusion criteria were included in this study. Data were obtained from the hospital medical record, and every case was conducted by 2 controls (normal delivery).It was found that woman age 19 years old and 35 years old showed the high risk trophoblastic. disease with odds ratio 7.85 and 6.6 respectively, parity 3-4 and . 5 increased the risk of trophoblastic disease with odds ratio 3.12 and 18.45 respectively, blood group A had odds ratio 3.17, and all of these variables showed statistically significant in bivariate analysis and multivariate analysis.Gravidity 4-5 and 6, last interval pregnancy 1-24 months and last pregnancy result with abortion had relative high odds ratio and statistically significant in bivariate analysis but not in multivariate analysis with stepwise logistic regression. There was a trend for increasing odds ratio with the increasing number of the history of spontaneous abortion, but not statistically significant.The study concluded that young (less than 19) and old (more than 35) women with high parity (more than 3), and with blood group A has a high risk to develop trophoblastic disease.Key words : pregnancy - trophoblastic disease - risk factor